Antimicrobial Activities of Bergamot, Lavender and Lemon Essential Oils for Homemade Perfume - Mohd Feza, Nur Syahzanani; Mohd Zawawi, Nurain Adlin; Mohd Ridzuan, Nur Rusydina; Abu Bakar, Norhaliza (Multidisciplinary Applied Research and Innovation, 2022)
Homemade perfume is commonly prepared from essential oil mixes in a tube, but it does not ensure human health safety. This project studied the antimicrobial activities of essential oils used to create the perfume and the perfume created by the Kirby-Bauer protocol. Three essential oils used in the test are the Citrus Limon (lemon), Citrus Bergamia (bergamot), and Lavandula (lavender). Staphylococcus aureus (S. Aureus) and Escherichia coli (E. Coli) were introduced as gram-positive and gram-negative bacteria growth on the Mannitol-Salt agar and Nutrient agar, respectively, with penicillin and ampicillin as positive controls and distilled water as a negative control. The antibiotics that acted as the positive control show that penicillin has better performance against S. Aureus than ampicillin against E. Coli. In comparing lemon and bergamot essential oils, the study found that lavender essential oil had strong antibacterial activity in both bacteria plates. However, the perfume showed no inhibitory effect in both antimicrobial activities as no inhibition zone was present after the test. In conclusion, this homemade perfume is not suggested to use by humans constantly for an extended period as it has an inferior performance against bacteria and can affect human health slowly.